A Study of Therapeutic Strategies in the Management of Diabetes Mellitus (DM) in India: Exploring the Potential of Solidifying Liquid SMEDDS for Improved Drug Delivery (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Most new chemical entities are poorly solubilized in water solubility has been a major issue for many decades, resulting to high intrasubjectintersubject variability in dosing, dosage inconsistency, and eventually low bioavailability. Solubility remains a major concern for formulation scientists despite several techniques such as solid dispersions and complexation with cyclodextrin, nanoparticles and permeation enhancers. As evidenced by various exploratory findings reported in literature, lipid formulations have emerged in recent years as a promising aid in improving the solubility of several lipophilic drugs. These findings show that lipid formulations can enhance absorption by facilitating the solubilized phases while decreasing the inherent restrictions of slow and curtailed drug dissolve rates in aqueous solutions. The self microemulsifying based drug delivery system (SMEDDS) has shown significant improvement in resolving solubility difficulties among lipid-based formulations. The oil, surfactant, cosurfactant, and drug constituents of SMEDDS produce an oil-in-water microemulsion when gently agitated in the stomach and intestine in vivo. SMEDDS are isotropic and thermodynamically stable solutions. SMEDDS has a greater interfacial surface area because of its small droplet size, which results in better release and absorption qualities. If you've ever taken a SMEDDS pill, you'll know that there are a few downsides, such as chemical and physical incompatibilities, drug outflow from the capsule shell, precipitation and ageing issues that can occur. Solid dosage forms don't have these kinds of difficulties, hence solidifying liquid SMEDDS via absorption into solid carriers is a viable option. Many studies have shown that changing liquid SMEDDS into solids and then into dosage forms like tablets, pellets, etc., is a viable option.